1998
DOI: 10.1074/jbc.273.26.15980
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Casein Kinase I ε and Casein Kinase I δ by anin Vivo Futile Phosphorylation Cycle

Abstract: Casein kinase I ␦ (CKI␦) and casein kinase I ⑀ (CKI⑀) have been implicated in the response to DNA damage, but the understanding of how these kinases are regulated remains incomplete. In vitro, these kinases rapidly autophosphorylate, predominantly on their carboxylterminal extensions, and this autophosphorylation markedly inhibits kinase activity (Cegielska, A., Gietzen, K. F., Rivers, A., and Virshup, D. M. (1998) J. Biol. Chem. 273, 1357-1364). However, we now report that while these kinases are able to auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 25 publications
4
115
1
Order By: Relevance
“…We first used just the catalytic domain of wild-type CKI , lacking the C-terminal regulatory domain [⌬CKI (wt)] to prevent potential confusion that could result from the autophosphorylation of this regulatory domain and the subsequent repression of CKI kinase activity. This use of the catalytic domain was also justified by evidence that CKI is kept in a dephosphorylated, active state in vivo (35).…”
Section: Resultsmentioning
confidence: 99%
“…We first used just the catalytic domain of wild-type CKI , lacking the C-terminal regulatory domain [⌬CKI (wt)] to prevent potential confusion that could result from the autophosphorylation of this regulatory domain and the subsequent repression of CKI kinase activity. This use of the catalytic domain was also justified by evidence that CKI is kept in a dephosphorylated, active state in vivo (35).…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal 125 amino acids of CK1␦ is ϳ50% identical to the corresponding domain of CK1⑀. In addition, several in vitro studies have found that the activity of CK1␦, like CK1⑀, is regulated by autophosphorylation (16,26). In vitro studies have also indicated that all three CK1␥ isoforms can be autophosphorylated (16), raising the possibility that these isoforms are regulated as well.…”
Section: Discussionmentioning
confidence: 99%
“…The hemagglutinin (HA)-tagged CKI was cloned in pCEP4 (Invitrogen) as previously described (39,40). Myc epitope-tagged PER1 and PER2, myc-CKI␦, and ␤TrCP(⌬Fbox) were subcloned into pCS2ϩMT as described (14,19).…”
Section: Methodsmentioning
confidence: 99%